Sex life and HPV: assessment of the knowledge level of a group of students from the public school system of Miracema (RJ) (Research, Society and Development, 2022)
The early start of sexual life is sometimes accompanied by risky sexual behaviors, such as not using condoms during sexual intercourse and a wide variety of partners, which place adolescents in a situation of vulnerability in the face of sexually transmitted infections, including those associated with Human Papillomavirus (HPV). Face to these assumptions, the present research aimed to evaluate the level of knowledge of adolescents in a public school in the city of Miracema (RJ). Through the application of a questionnaire with 24 questions, it was found a lack of knowledge about aspects of sexual life, as well as about HPV, the lack of dialogue about the theme in the family and at school, which exposes them to seek erroneous and mistaken information from unsafe sources, which contributes to enhance their vulnerability to risk situations.